2019
DOI: 10.21037/jtd.2019.07.06
|View full text |Cite
|
Sign up to set email alerts
|

Current indications and outcomes for thoracoscopic segmentectomy for early stage lung cancer

Abstract: Contemporary literature has many reports as to whether thoracoscopic segmentectomy is the best lung-sparing operation for early stage lung cancer, both in terms of oncologic efficacy and morbidity. Wedge resections were also evaluated against both lobectomies and segmentectomies, offering comparable survival with some caveats (size of the margins, histologic type, solid component, lymph node

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…[13][14][15][16][17] However, in the case of technically demanding operations like segmentectomy, one might question whether VATS is associated with procedural adverse events, which may eventually mitigate the benefits of the minimally invasive nature of the operation. Our study showed that despite being more technically demanding compared to other VATS operation, 18 VATS segmentectomy is associated with lower rates of postoperative complications when compared to thoracotomy segmentectomy.…”
Section: Discussionmentioning
confidence: 59%
“…[13][14][15][16][17] However, in the case of technically demanding operations like segmentectomy, one might question whether VATS is associated with procedural adverse events, which may eventually mitigate the benefits of the minimally invasive nature of the operation. Our study showed that despite being more technically demanding compared to other VATS operation, 18 VATS segmentectomy is associated with lower rates of postoperative complications when compared to thoracotomy segmentectomy.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies have shown that NSCLC patients that received segmentectomies for lesions < 2 cm had similar oncologic effects compared with those that received lobectomies [8,9,10,11]. Patients receiving segmentectomies also had more protected lung function [12,13]. The NCCN guidelines indicate that the standard recommendation for the treatment of early NSCLC patients is anatomic pulmonary resection.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic segmentectomy is an alternative strategy for management of small pulmonary lesions. Ideal lesions for segmentectomy are peripheral, less than 2 cm in size, and well centered within the target segment in order to achieve appropriate margins (26)(27)(28)(29)(30)(31). Caution should be taken for lesions that cross intersegmental planes, as margins are unlikely to be adequate (26).…”
Section: Segmentectomymentioning
confidence: 99%